A clinical study of hyperreactive airway disease with wheeze in children aged five to twelve years with special reference to pulmonary function test - Reddy, Arjun; Patel, Abhishek; Chetty, Sanjeev (International Journal of Contemporary Pediatrics, 2019)
Background: Pulmonary function test is the easiest and most cost-effective method to evaluate respiratory functions. PFT can be measured by a simple instrument spirometer. Measuring PFT has been suggested as an important tool in understanding HRAD and its complications and management by all international guidelines. The objectives of this study were to clinically diagnose the hyperreactive airway disease in children coming to Navodaya Medical College, Raichur, of age group 5 to 12 years. And to perform pulmonary function test before and after the use of a bronchodilator. Methods: PFT was measured in 100 children who came with HRAD with wheeze using Spiro lab III spirometer. The child was given then nebulization with salbutamol and PFT was performed again after 30 min. Results: A total of 100 clinically diagnosed cases of HRAD of age group 5 to 12 years of both the gender was taken into the study, of which more than 44% of the children showed more than 20% improvement in parameters FEV1, PEF, FVC and marginal improvement in EV1/FVC post bronchodilator compared to their prebronchodilator parameters. The young children of both the gender showed better improvement than elder children. Conclusions: Spirometry is the best tool to assess HRAD even in younger children, early diagnosis and regular follow up with PFT helps to understand and prevent the progression of the disease with prompt treatment.